Catalytic Models of Tyrosinase: Reactivity Differences between Systems Based on Mono‐ and Binucleating Ligands. Issue 21 (2nd April 2015) - Schottenheim, Julia; Gernert, Claus; Herzigkeit, Benjamin; Krahmer, Jan; Tuczek, Felix
Abstract: A new tyrosinase model based on the binucleating ligand Lpy 2 is synthesized and characterized. The ligand Lpy 2 contains a combination of an imine and a pyridine function in the sidearms, which are bridged by a flexible alkyl spacer. As shown by UV/Vis and NMR spectroscopy, the Cu2 Lpy 2 complex catalyzed the conversion of the monophenol 2, 4‐di‐ tert ‐butylphenol (DTBP‐H) into the o ‐quinone 3, 5‐di‐ tert ‐butylquinone (DTBQ) with a turnover number (TON) of 18. The dicopper complex of Lpy 2 thus shows monophenolase activity that is comparable to that of the recently developed Lpy 1 model of tyrosinase, which is based on a known mononucleating ligand (M. Rolff, J. Schottenheim, G. Peters, F. Tuczek, Angew. Chem. Int. Ed. 2010, 122, 6583). The electron‐poor substrate 4‐hydroxybenzoic acid methyl ester (MeBA‐OH), in contrast, is converted by Cu2 Lpy 2 into the semiquinone. For both substrates, the oxygenation reactions were also conducted in a stoichiometric fashion to obtain information on the intermediates involved. For the substrate MeBA‐OH, we detected a binuclear μ‐catecholato copper(II) complex by high‐resolution ESI mass spectrometry. These studies were complemented by investigations of deactivation mechanisms that could be invoked to explain the limitation of the TON. To this end, a bis‐μ‐hydroxido Lpy 2 dicopper(II) complex as well as a semiquinone Lpy 2 complex were prepared. Both complexes may represent decay products of the catalyst. Abstract : A tyrosinase model based on the binucleating ligand Lpy 2 was developed and characterized. The ligand Lpy 2 contains a combination of an imine and a pyridine function in the sidearms that are bridged by a flexible alkyl spacer. The Cu2 Lpy 2 complex catalyzes the conversion of monophenol DTBP‐H into the o ‐quinone DTBQ (TON = 18). An electron‐poor substrate is converted into the semiquinone.